The use of caffeine as a respiratory stimulant in a cat. Issue 4 (24th February 2022) - Kennedy, Christopher R.; Wayne, Annie S.; Rozanski, Elizabeth A.
Abstract: Objective: To report the use of caffeine as a respiratory stimulant in a cat with hypoventilation. Case summary: A cat was mechanically ventilated due to persistent hypercapnia (Pet co 2  > 75 mm Hg) following median sternotomy and thymectomy. After 3 days of mechanical ventilatory support, the cat would initiate breaths but failed weaning due to persistent hypercapnia. Following administration of intravenous caffeine (total 12 mg/kg over 24 h), respiratory and mental status rapidly improved. The cat was subsequently extubated and able to maintain Pvco 2  < 50 mm Hg. The cat was later diagnosed with myasthenia gravis. Quality of life 13 months after discharge was reported as excellent by her owner. New or unique information provided: Caffeine may be considered as a respiratory stimulant in cats with hypoventilation.